Altered gene expression of epigenetic modifying enzymes in response to dietary supplementation with linseed oil. Issue 2 (19th May 2017) - Li, Ran; Ibeagha-Awemu, Eveline M.
Abstract : Recently we showed that 5% linseed oil (LSO) and 5% safflower oil (SFO) supplementation of cow's diets reduced milk fat yield by 30·38 and 32·42% respectively, accompanied by differential expression of genes and regulation by microRNAs (miRNA). This research communication addresses the hypothesis that epigenetic regulation could be involved in the observed milk fat reduction. Thus, this study investigated the gene expression pattern of major epigenetic modifying enzymes in response to dietary supplementation with LSO or SFO. Twenty-six Canadian Holstein cows in mid lactation were randomly assigned to two groups (13/group) and fed a control diet for 28 d (day −28 to −1) (control period- CP) followed by a treatment period (TP) (control diet supplemented with 5% LSO (LSO treatment) or 5% SFO (SFO treatment) of 28 d (day +1 to +28). After treatment, cows in the two groups were returned to the control diet for another 28 d (day +29 to +56) (post treatment period-PTP). Milk samples were collected on day −1 (CP), +7, +28 (TP) and +56 (PTP) for RNA isolation and measurement of the expression of thirteen epigenetic modifying genes including two DNA methytrasferases ( DNMT1, DNMT3A ), four histone acetylases ( HAT1, KAT2A, KAT5 and CREBBP ), five histone deacetylases ( HDAC1, HDAC2, HDAC3, SIRT1 and SIRT2 ) and two histone methytransferases ( EHMT2 and PRMT1 ) by qPCR. Linseed oil supplementation significantly repressed the expression of EHMT2, HDAC2 and HDAC3 on day +7 ( P < 0·05) and KAT2A and SIRT2 on day +28 ( P < 0·05) as compared with the control period (day −1) while SFO had no effect. When LSO was withdrawn, the expression of some of the genes increased slightly but did not reach control (day −1) levels at the end of the PTP. Our study demonstrated a significant role of LSO in the epigenetic regulation of fatty acid synthesis as compared to SFO. The effect of LSO may be related to its higher degree of unsaturation and might represent a different regulatory mechanism which needs further investigation.